A water-based one-component PP conductive primer and preparation method thereof

By using raw materials such as water-based epoxy resin and conductive mica powder in aqueous single-component PP conductive primer, the problem of poor mechanical properties of its coating film is solved, and better adhesion, wear resistance and scratch resistance are achieved, which extends service life and expands application.

CN118725680BActive Publication Date: 2025-04-04HUIZHOU JUXIN CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410921897.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-04-04
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

The coating of water-based single-component PP conductive primer has poor mechanical properties and requires frequent maintenance or surface reinforcement, which in turn reduces its application.

Method used

The aqueous epoxy resin, conductive mica powder, conductive carbon black, modified ceramic clay, nano-silica, modified graphene and other raw materials are used to form an aqueous single-component PP conductive primer with improved mechanical properties through specific ratios and treatment methods.

Benefits of technology

It improves the mechanical properties of the coating of the water-based single-component PP conductive primer, enhances its adhesion, wear resistance and scratch resistance, extends its service life and expands its application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of conductive primers, and specifically discloses a water-based one-component PP conductive primer and a preparation method thereof. The water-based one-component PP conductive primer comprises the following raw materials: 50-60 parts of water-based epoxy resin, 20-30 parts of conductive mica powder, 45-55 parts of deionized water, 3-5 parts of conductive carbon black, 15-20 parts of modified china clay, 5-8 parts of nano-silicon dioxide, 0.1-0.6 parts of modified graphene, 3-5 parts of silane coupling agent, 3-8 parts of ethyl acetate, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent. The water-based one-component PP conductive primer prepared in the present application has good mechanical properties, wear resistance and adhesion, so that the PP conductive primer has good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive primers, and more specifically, to a water-based single-component PP conductive primer and a preparation method thereof. Background Art

[0002] Conductive primer is a special type of coating that contains conductive fillers such as carbon black, metal particles (such as silver, copper) or nanomaterials. These particles form a continuous conductive path in the coating and are conductive, thus having anti-static and anti-electromagnetic interference properties. It is commonly found in electronic equipment, automotive parts, aerospace, packaging and flooring, etc., to prevent static electricity accumulation and protect sensitive electronic components.

[0003] Water-based one-component PP conductive primer is an environmentally friendly coating, mainly used for the surface of polypropylene (PP) material, providing conductive properties, with the characteristics of simple construction, quick drying, chemical resistance and excellent conductive properties. However, the coating film of water-based one-component PP conductive primer has poor mechanical properties and requires frequent maintenance or surface enhancement treatment, which reduces the application of water-based one-component PP conductive primer. Summary of the invention

[0004] In order to improve the problem of poor mechanical properties of the coating film of a water-based one-component PP conductive primer, the present application provides a water-based one-component PP conductive primer and a preparation method thereof.

[0005] In the first aspect, the present application provides a water-based one-component PP conductive primer, which adopts the following technical scheme: a water-based one-component PP conductive primer, comprising the following raw materials: 50-60 parts of water-based epoxy resin, 20-30 parts of conductive mica powder, 45-55 parts of deionized water, 3-5 parts of conductive carbon black, 15-20 parts of modified kaolin, 5-8 parts of nano-silica, 0.1-0.6 parts of modified graphene, 3-5 parts of silane coupling agent, 3-8 parts of ethyl acetate, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent.

[0006] By adopting the above technical scheme, the water-based epoxy resin has good adhesion, can be tightly attached to the substrate, and provides a solid attachment basis for the conductive particles. It also has good chemical resistance and corrosion resistance, can protect the substrate from erosion by environmental factors, and enhance the protective effect of the substrate. Moreover, the water-based epoxy resin can be used as a carrier for conductive mica powder and conductive carbon black to ensure that these particles are evenly distributed in the coating film to form a continuous conductive network, thereby providing good conductive properties. The water-based epoxy resin has a low VOC (volatile organic compound) content and meets environmental protection requirements.

[0007] Conductive mica powder combines with water-based epoxy resin to form a conductive network, providing anti-static or electromagnetic shielding functions. Conductive mica powder can also increase the thickness and toughness of the primer, and improve the crack resistance and wear resistance of the primer. The surface of the mica powder can also form a good bond with the water-based epoxy resin, which helps to improve the adhesion between the primer and the substrate. Conductive carbon black is a highly dispersed tiny particle that forms a continuous conductive path in the primer, giving the primer good conductive properties for anti-static or electromagnetic shielding. Conductive carbon black can also be loaded in the pores of the conductive mica powder to increase the wear resistance and adhesion of the primer.

[0008] Modified kaolin can adjust the viscosity and rheology of the primer, help achieve better leveling and coverage during the coating process, improve construction performance, help improve the adhesion of the primer coating, and also increase the hardness, wear resistance and scratch resistance of the primer coating; nano-silica helps to improve the dispersion of modified kaolin, conductive mica powder and conductive carbon black in the primer, prevent precipitation and agglomeration, and improve the stability of the primer; it can also improve the hardness, wear resistance and scratch resistance of the primer coating, and increase the mechanical strength of the primer coating; it can also improve the dispersion of conductive mica powder and conductive carbon black, indirectly enhance the conductive properties of the primer, and ensure the continuity of the conductive network; it can improve the adhesion of the primer to the substrate and improve the adhesion of the primer coating.

[0009] Modified graphene has extremely high electrical conductivity, which can significantly improve the conductivity of primer coatings and is used in electromagnetic shielding, antistatic and conductive connection applications; modified graphene has high strength and high toughness, which can enhance the mechanical properties of primer coatings, such as wear resistance, crack resistance and adhesion. Modified graphene can be loaded on the surface and pores of modified porcelain clay, thereby improving the mechanical properties, adhesion and conductivity of the system; one end of the silane coupling agent reacts with the conductive mica powder and the other end combines with the water-based epoxy resin matrix to enhance the adhesion between the conductive mica powder and the water-based epoxy resin, thereby improving the bonding strength of the primer coating.

[0010] Optionally, the method for preparing the modified porcelain clay comprises the following steps:

[0011] (1) calcining the china clay at 500-600° C. for 2-3 h, dispersing the china clay in deionized water, adding sodium humate, ball milling for 6-8 h, sieving, washing with water, and drying to obtain pretreated china clay;

[0012] (2) The modified glass fiber is crushed, sieved, and then dispersed in deionized water, and the china clay pretreated in step (1) is added, stirred for 2-3 hours, filtered, and chitosan solution is sprayed on the surface, and dried to obtain modified china clay.

[0013] By adopting the above technical solution, the porcelain clay is calcined to remove moisture from the porcelain clay and decompose the organic matter therein, thereby increasing the specific surface area, mechanical strength and wear resistance of the porcelain clay. Sodium humate changes the properties of the surface of the porcelain clay particles, increases the binding force between the particles, reduces the friction between the particles, and improves the fluidity of the porcelain clay particles, which facilitates subsequent mixing with other components.

[0014] Modified glass fiber has high strength and toughness, and can significantly improve the mechanical strength of porcelain clay, such as tensile strength, flexural strength and impact resistance. The modified glass fiber is loaded on the surface and pores of the porcelain clay to form a continuous fiber network, which improves the toughness of the porcelain clay, prevents cracks, and helps to improve the cracking of the primer later.

[0015] Chitosan has film-forming properties and can cover porcelain clay, making the modified glass fiber and porcelain clay tightly bonded, improving the molding stability and structural strength of chitosan. There is a synergistic effect between porcelain clay, modified glass fiber and chitosan, which together improve the mechanical properties and crack resistance of porcelain clay, which is helpful for the subsequent application of primer.

[0016] Optionally, the mass ratio of the china clay, modified glass fiber and chitosan solution is 1:0.2-0.4:0.05-0.07.

[0017] By adopting the above technical scheme, the mass ratio of porcelain clay, modified glass fiber and chitosan solution is further limited within a certain range, thereby improving the mechanical properties, adhesion and crack resistance of porcelain clay. The modified glass fiber has high strength and toughness, which improves the mechanical strength of porcelain clay such as tensile strength, flexural strength and impact resistance. Chitosan has film-forming properties and can coat porcelain clay, so that the modified glass fiber and porcelain clay are tightly bonded, thereby improving the mechanical properties and crack resistance of porcelain clay, which is conducive to the subsequent application of primer.

[0018] Optionally, the preparation method of the modified glass fiber comprises the following steps: dispersing the glass fiber in a sodium hydroxide solution, stirring for 20-30 minutes, washing with water, and then dispersing it in deionized water, adding carbon fiber, bentonite and sodium alginate, stirring at a temperature of 90-95°C for 2-3 hours, and drying to obtain the modified glass fiber.

[0019] By adopting the above technical solution, sodium hydroxide erodes the surface of the glass fiber, improving the adhesion between the glass fiber and other matrix materials. Carbon fiber has excellent conductivity and high strength, and can be loaded on the surface of the glass fiber to improve the tensile strength, wear resistance and impact toughness of the glass fiber, making the primer coating more durable. Subsequent application of carbon fiber in the primer can form a conductive network, reduce the resistance of the primer coating, and cooperate with other conductive fillers to improve the antistatic or electromagnetic shielding effect.

[0020] Bentonite has good adsorption properties. Glass fiber and carbon fiber can be loaded in the pores of bentonite, which improves the crack resistance and compressive strength of the system. It is subsequently used in primers to improve the rheological properties of the primer system, prevent precipitation or stratification, help the adhesion between the primer and the substrate, and improve the adhesion of the coating. It can also work with conductive fillers to improve the mechanical properties and durability of the primer coating.

[0021] Sodium alginate has good adhesion, which allows glass fiber, carbon fiber and bentonite to adhere tightly, thereby helping to stabilize the performance of the modified glass fiber. In addition, sodium alginate, as a carrier of conductive particles, helps to disperse and stabilize conductive fillers, promotes the formation of a conductive network, and can also improve the adhesion between the primer and the substrate, thereby enhancing the adhesion performance of the primer coating.

[0022] Optionally, the mass ratio of the glass fiber, carbon fiber, bentonite and sodium alginate is 1:0.2-0.4:0.1-0.3:0.07-0.09.

[0023] By adopting the above technical scheme, the mass ratio of glass fiber, carbon fiber, bentonite and sodium alginate is further limited within a certain range, the mechanical properties, electrical conductivity and wear resistance of glass fiber are improved, glass fiber and carbon fiber can be loaded in the pores of bentonite, the tensile strength, wear resistance, crack resistance and compressive strength of the system are improved, sodium alginate has good adhesion, so that the glass fiber, carbon fiber and bentonite are tightly bonded, which helps to stabilize the performance of the modified glass fiber, so that the obtained modified glass fiber has better mechanical properties and adhesion, and improves the adhesion performance between the subsequent primer and the substrate.

[0024] Optionally, the method for preparing the modified graphene comprises the following steps:

[0025] (1) dispersing graphene in a formic acid solution, ultrasonically treating for 1-2 hours, washing with water, and then dispersing graphene in deionized water, adding sodium dodecylbenzene sulfonate, and ultrasonically treating for 2-3 hours to obtain a mixed solution;

[0026] (2) Dispersing conductive white carbon black in butanol, stirring evenly, adding the mixed solution of step (1), ultrasonicating for 2-3 hours, then adding modified lignin, stirring at 40-45° C. for 2-3 hours, and drying to obtain modified graphene.

[0027] By adopting the above technical solution, graphene is dispersed in a formic acid solution, and sodium dodecylbenzene sulfonate improves the dispersibility of graphene in the formic acid solution and prevents graphene from agglomerating due to electrostatic interaction.

[0028] Conductive silica can be loaded on the surface of graphene, which helps to disperse graphene in the matrix, prevent graphene sheets from agglomerating, and form a more efficient conductive network, thereby improving the hardness, toughness and adhesion of the system. Subsequent application in primers not only improves the conductivity of the primer, but also increases the hardness, wear resistance and adhesion of the primer.

[0029] The modified lignin has a certain viscosity, which makes the conductive white carbon black and graphene adhere closely, thereby stabilizing the performance of the modified graphene and enhancing the toughness and strength of the graphene. At the same time, the thermal stability and corrosion resistance of the modified lignin can also improve the durability of the primer. The modified lignin helps the formation of the graphene network and improves the conductivity of the primer.

[0030] Optionally, the mass ratio of the graphene, conductive white carbon black and modified lignin is 1 mg: 3-5 g: 0.2-0.4 g.

[0031] By adopting the above technical scheme, the mass ratio of graphene, conductive silica and modified lignin is further limited within a certain range, thereby improving the mechanical properties and conductivity of graphene. Conductive silica can be loaded on the surface of graphene to form a more efficient conductive network, thereby improving the hardness, toughness and adhesion of the system. Modified lignin allows conductive silica and graphene to adhere tightly, thereby enhancing the toughness and strength of graphene. The combination of graphene, conductive silica and modified lignin has a synergistic effect, and subsequent application in primers not only improves the conductivity of the primers, but also increases the hardness, wear resistance and adhesion of the primers.

[0032] Preferably, the preparation method of the modified lignin comprises the following steps: dispersing the lignin in a sodium hydroxide solution, stirring at 80-85° C. for 1-2 hours, adding dimethylphenol, reacting for 1-2 hours, filtering, washing with water, and then dispersing in an acetic acid solution, adding nano-silver powder and polyvinyl alcohol, stirring for 1-2 hours, and drying to obtain the modified lignin.

[0033] By adopting the above technical scheme, sodium hydroxide removes sticky substances on the surface of lignin, dimethylphenol undergoes alkylation reaction with the phenolic hydroxyl group of lignin to form ether bonds to improve the solubility and thermal stability of lignin, and then acetic acid further treats the surface of lignin to promote the hydrolysis of lignin and help mix lignin with other components.

[0034] Nano-silver powder can be loaded on the surface and pores of lignin to improve the antibacterial and electrical conductivity of lignin. It can be subsequently applied to primer to form a continuous conductive network with good electrical conductivity to prevent static electricity accumulation and electromagnetic interference. The high surface area of ​​nano-silver increases the contact between the primer and the substrate, which helps to improve the adhesion of the coating.

[0035] Polyvinyl alcohol and lignin can form a network structure through physical cross-linking, which increases the mechanical strength and toughness of the system, improves the adhesion of the system, and makes the nano-silver powder and lignin adhere tightly, and subsequently improves the viscosity, mechanical properties and conductivity of the modified lignin, thereby effectively improving the corresponding performance of the primer.

[0036] Preferably, the mass ratio of the lignin, nano silver powder and polyvinyl alcohol is 1:0.3-0.5:0.04-0.07.

[0037] By adopting the above technical scheme, the mass ratio of lignin, nano-silver powder and polyvinyl alcohol is further limited within a certain range, the mechanical properties, viscosity and conductivity of lignin are improved, the nano-silver powder can be loaded on the surface and pores of lignin, the antibacterial and electrical conductivity of lignin are improved, polyvinyl alcohol and lignin can form a network structure through physical cross-linking, the mechanical strength and toughness of the system are increased, the nano-silver powder and lignin are tightly bonded, and the viscosity, mechanical properties and conductivity of the modified lignin are subsequently improved, thereby effectively improving the corresponding performance of the primer.

[0038] In a second aspect, the present application provides a method for preparing a water-based one-component PP conductive primer, comprising the following steps: mixing conductive mica powder, conductive carbon black, modified kaolin, nano-silica, and modified graphene, and grinding to obtain a mixture; mixing water-based epoxy resin, deionized water, silane coupling agent, ethyl acetate, leveling agent, and defoaming agent evenly, adding the mixture, and stirring for 2-3 hours at a stirring speed of 2000-2200 r / min to obtain a water-based one-component PP conductive primer.

[0039] By adopting the above technical scheme, the present application mixes the various raw material components, the production process is simple, the preparation efficiency is high, and a water-based single-component PP conductive primer with excellent performance in all aspects is obtained, thereby improving the application of the water-based single-component PP conductive primer.

[0040] In summary, this application has the following beneficial effects:

[0041] 1. The water-based epoxy resin in this application has good adhesion, can be tightly attached to the substrate, and provides a solid attachment basis for the conductive particles. It also has good chemical resistance and corrosion resistance, can protect the substrate from erosion by environmental factors, and enhance the protective effect of the substrate.

[0042] 2. The modified kaolin in this application can adjust the viscosity and rheology of the primer, help achieve better leveling and coverage during the coating process, improve construction performance, help improve the adhesion of the primer coating, and also increase the hardness, wear resistance and scratch resistance of the primer coating.

[0043] 3. The modified graphene in this application has extremely high electrical conductivity, which can significantly improve the conductive properties of the primer coating and is used for electromagnetic shielding, antistatic and conductive connection applications; the modified graphene has high strength and high toughness, which can enhance the mechanical properties of the primer coating, such as wear resistance, crack resistance and adhesion. The modified graphene can be loaded on the surface and pores of the modified porcelain clay, thereby improving the mechanical properties, adhesion and conductivity of the system. DETAILED DESCRIPTION

[0044] Preparation example of modified porcelain clay

[0045] Preparation Example 1-1

[0046] The preparation method of modified porcelain clay comprises the following steps:

[0047] (1) 2.3 kg of china clay was calcined at 550° C. for 3 h, then dispersed in 5.1 L of deionized water, 0.8 kg of sodium humate was added, ball milled for 8 h, passed through a 30-mesh sieve, washed with water, and dried to obtain pretreated china clay;

[0048] (2) The modified glass fiber was crushed, passed through a 10-mesh sieve, and then dispersed in 2.5 L of deionized water, and the china clay pretreated in step (1) was added, stirred for 3 h, filtered, and the chitosan solution was sprayed on the surface, and dried to obtain modified china clay.

[0049] The mass ratio of china clay, modified glass fiber and chitosan solution is 1:0.2:0.05.

[0050] The preparation method of modified glass fiber comprises the following steps: dispersing 1.5 kg of glass fiber in 2 L of 10% sodium hydroxide solution by mass, stirring for 25 min, washing with water, and then dispersing in 3 L of deionized water, adding carbon fiber, bentonite and sodium alginate, stirring at a temperature of 95° C. for 3 h, and drying to obtain modified glass fiber.

[0051] The mass ratio of glass fiber, carbon fiber, bentonite and sodium alginate is 1:0.4:0.3:0.09.

[0052] Preparation Example 1-2

[0053] The difference from Preparation Example 1-1 is that in step (2), no modified glass fiber is added.

[0054] Preparation Example 1-3

[0055] The difference from Preparation Example 1-1 is that in step (2), the chitosan solution is not sprayed.

[0056] Preparation Example 1-4

[0057] The difference from Preparation Example 1-1 is that the mass ratio of china clay, modified glass fiber and chitosan solution is 1:0.4:0.07.

[0058] Preparation Example 1-5

[0059] The difference from Preparation Example 1-1 is that the mass ratio of china clay, modified glass fiber and chitosan solution is 1:0.1:0.15.

[0060] Preparation Example 1-6

[0061] The difference from Preparation Example 1-1 is that no carbon fiber is added in the preparation method of the modified glass fiber.

[0062] Preparation Example 1-7

[0063] The difference from Preparation Example 1-1 is that bentonite is not added in the preparation method of the modified glass fiber.

[0064] Preparation Example 1-8

[0065] The difference from Preparation Example 1-1 is that sodium alginate is not added in the preparation method of the modified glass fiber.

[0066] Preparation Example 1-9

[0067] The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, carbon fiber, bentonite and sodium alginate is 1:0.2:0.1:0.07.

[0068] Preparation Example 1-10

[0069] The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, carbon fiber, bentonite and sodium alginate is 1:0.7:0.05:0.12.

[0070] Preparation example of modified graphene

[0071] Preparation Example 2-1

[0072] The preparation method of modified graphene comprises the following steps:

[0073] (1) 1.5 g of graphene was dispersed in 2 L of 12% formic acid solution, ultrasonicated for 2 h, washed with water, and then dispersed in 2.2 L of deionized water, 0.2 kg of sodium dodecylbenzene sulfonate was added, and ultrasonicated for 3 h to obtain a mixed solution;

[0074] (2) Disperse conductive white carbon black in 9 L of butanol, stir evenly, add the mixed solution of step (1), ultrasonicate for 3 h, then add modified lignin, stir at 45 ° C for 3 h, and dry to obtain modified graphene.

[0075] The mass ratio of graphene, conductive silica and modified lignin is 1 mg:3 g:0.2 g.

[0076] The preparation method of modified lignin comprises the following steps: dispersing 1.5 kg of lignin in 2 L of sodium hydroxide solution with a mass fraction of 10%, stirring at 85° C. for 2 hours, adding 0.2 kg of dimethylphenol, reacting for 2 hours, filtering, washing with water, and then dispersing in 2 L of acetic acid solution with a mass concentration of 4%, adding nano silver powder and polyvinyl alcohol, stirring for 2 hours, and drying to obtain modified lignin.

[0077] The mass ratio of lignin, nano-silver powder and polyvinyl alcohol is 1:0.5:0.07.

[0078] Preparation Example 2-2

[0079] The difference from Preparation Example 2-1 is that in step (2), no conductive white carbon black is added.

[0080] Preparation Example 2-3

[0081] The difference from Preparation Example 2-1 is that in step (2), no modified lignin is added.

[0082] Preparation Example 2-4

[0083] The difference from Preparation Example 2-1 is that the mass ratio of graphene, conductive white carbon black and modified lignin is 1 mg:5 g:0.4 g.

[0084] Preparation Example 2-5

[0085] The difference from Preparation Example 2-1 is that the mass ratio of graphene, conductive white carbon black and modified lignin is 1 mg:1 g:0.9 g.

[0086] Preparation Example 2-6

[0087] The difference from Preparation Example 2-1 is that in the preparation method of the modified lignin, no nano silver powder is added.

[0088] Preparation Example 2-7

[0089] The difference from Preparation Example 2-1 is that polyvinyl alcohol is not added in the preparation method of the modified lignin.

[0090] Preparation Example 2-8

[0091] The difference from Preparation Example 2-1 is that the mass ratio of lignin, nano silver powder and polyvinyl alcohol is 1:0.3:0.04.

[0092] Preparation Example 2-9

[0093] The difference from Preparation Example 2-1 is that the mass ratio of lignin, nano silver powder and polyvinyl alcohol is 1:0.1:0.15.

[0094] Example

[0095] Example 1

[0096] A water-based single-component PP conductive primer includes the following raw materials: 60kg of water-based epoxy resin, 30kg of conductive mica powder, 45kg of deionized water, 3kg of conductive carbon black, 15kg of modified china clay, 5kg of nano-silicon dioxide, 0.1kg of modified graphene, 3kg of silane coupling agent, 3kg of ethyl acetate, 0.5kg of leveling agent, and 0.5kg of defoaming agent. The leveling agent is HTK-2020 polyurethane leveling agent, and the defoaming agent is 2082 polyether defoaming agent.

[0097] The preparation method of the water-based single-component PP conductive primer comprises the following steps: mixing and grinding conductive mica powder, conductive carbon black, modified china clay, nano silicon dioxide and modified graphene to obtain a mixture;

[0098] The water-based epoxy resin, deionized water, silane coupling agent, ethyl acetate, leveling agent and defoaming agent were evenly mixed, added to the mixture, and stirred for 3 hours at a stirring speed of 2200 r / min to obtain a water-based one-component PP conductive primer.

[0099] The modified kaolin was prepared according to Preparation Example 1-1, and the modified graphene was prepared according to Preparation Example 2-1.

[0100] Example 2

[0101] A water-based one-component PP conductive primer, which differs from Example 1 in that it comprises the following raw materials: 50 kg of water-based epoxy resin, 20 kg of conductive mica powder, 55 kg of deionized water, 5 kg of conductive carbon black, 20 kg of modified kaolin, 8 kg of nano-silicon dioxide, 0.6 kg of modified graphene, 5 kg of silane coupling agent, 8 kg of ethyl acetate, 1 kg of leveling agent, and 1 kg of defoaming agent.

[0102] Example 3

[0103] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-2.

[0104] Example 4

[0105] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-3.

[0106] Example 5

[0107] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Examples 1-4.

[0108] Example 6

[0109] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-5.

[0110] Example 7

[0111] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-6.

[0112] Example 8

[0113] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-7.

[0114] Example 9

[0115] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay is prepared as in Preparation Example 1-8.

[0116] Example 10

[0117] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-9.

[0118] Embodiment 11

[0119] A water-based one-component PP conductive primer is different from Example 1 in that the modified porcelain clay adopts Preparation Example 1-10.

[0120] Example 12

[0121] A water-based one-component PP conductive primer, which is different from Example 1 in that the modified graphene adopts Preparation Example 2-2.

[0122] Example 13

[0123] A water-based one-component PP conductive primer, which is different from Example 1 in that the modified graphene adopts Preparation Example 2-3.

[0124] Embodiment 14

[0125] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-4.

[0126] Embodiment 15

[0127] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-5.

[0128] Example 16

[0129] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-6.

[0130] Embodiment 17

[0131] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-7.

[0132] Embodiment 18

[0133] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-8.

[0134] Embodiment 19

[0135] A water-based one-component PP conductive primer is different from Example 1 in that the modified graphene adopts Preparation Example 2-9.

[0136] Comparative Example

[0137] Comparative Example 1

[0138] A water-based one-component PP conductive primer, which differs from Example 1 in that modified china clay is not added.

[0139] Comparative Example 2

[0140] A water-based one-component PP conductive primer, which differs from Example 1 in that the modified china clay is replaced by an equal amount of china clay.

[0141] Comparative Example 3

[0142] A water-based one-component PP conductive primer, which differs from Example 1 in that modified graphene is not added.

[0143] Comparative Example 4

[0144] A water-based one-component PP conductive primer, which differs from Example 1 in that the modified graphene is replaced by an equal amount of graphene.

[0145] Performance testing

[0146] The water-based one-component PP conductive primers prepared in Examples 1-19 and Comparative Examples 1-4 were subjected to performance tests;

[0147] Use a digital multimeter to test the table dry conductivity time;

[0148] Adhesion test reference standard GB / T 9286;

[0149] The test reference standard for water-resistant adhesion (40°C, 10d) is GB / T 9286;

[0150] The impact resistance test refers to the standard ASTM D2794, conditions: 25°C, 4.9N, the height of the weight when evaluating the coating cracking; the flexibility test refers to the standard ASTM D522, bending the coating to check whether it cracks. The test results are shown in Table 1.

[0151] Table 1 Test data of embodiments and comparative examples

[0152]

[0153]

[0154] Combining the examples and the data in Table 1, it can be seen that the water-based one-component PP conductive primers prepared in Examples 1-2, Example 5, Example 10, Example 14 and Example 18 have good mechanical properties, adhesion and surface dry conductivity time. Among them, the surface dry conductivity time of Example 1 is 4 minutes, the adhesion is level 0, the adhesion after water resistance is level 0, and there is no blistering or falling off, the impact resistance is 50 cm, and the flexibility is 1 mm, indicating that the various components in the present application cooperate with each other to improve the conductivity, adhesion and mechanical properties of the primer coating, thereby extending the service life of the primer and expanding the application of the water-based one-component PP conductive primer.

[0155] In the preparation method of modified porcelain clay in Example 3, modified glass fiber is not added. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time is 8 minutes, the adhesion is level 1, the adhesion after water resistance is level 1, and there is no blistering or falling off, the impact resistance is 40 cm, and the flexibility is 2 mm, indicating that the modified glass fiber has high strength and toughness, and can significantly improve the mechanical strength of the porcelain clay such as tensile strength, flexural strength and impact resistance, thereby improving the mechanical properties of the primer.

[0156] In the preparation method of modified kaolin in Example 4, chitosan solution is not sprayed. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time is 7 min, the impact resistance is 45 cm, and the flexibility is 2 mm, indicating that chitosan coating modified glass fiber and kaolin improves the mechanical properties and crack resistance of kaolin, which helps to subsequently improve the corresponding performance of the primer.

[0157] Example 6 changes the mass ratio of china clay, modified glass fiber and chitosan solution. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time, impact resistance and flexibility performance tests are all worse than those of Example 1, but better than those of Examples 3-4, indicating that there is a synergistic effect between china clay, modified glass fiber and chitosan, which improves the mechanical properties, adhesion and crack resistance of china clay, and is helpful for the subsequent application of primer.

[0158] In the preparation method of the modified glass fiber of Example 7, no carbon fiber is added, in the preparation method of the modified glass fiber of Example 8, no bentonite is added, and in the preparation method of the modified glass fiber of Example 9, no sodium alginate is added. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time, adhesion, impact resistance and flexibility tests are all worse than those of Example 1 to varying degrees, but better than those of Example 3, indicating that the carbon fiber has excellent conductivity and high strength, can be loaded on the surface of the glass fiber, and improves the tensile strength, wear resistance and impact toughness of the glass fiber; bentonite has good adsorption, and the glass fiber and carbon fiber can be loaded in the pores of bentonite, which improves the crack resistance and compressive strength of the system; sodium alginate has good adhesion, so that the glass fiber, carbon fiber and bentonite are tightly bonded, which helps to stabilize the performance of the modified glass fiber.

[0159] Example 11 changes the mass ratio of glass fiber, carbon fiber, bentonite and sodium alginate. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time, impact resistance and flexibility performance tests are all worse than those of Example 1, but better than those of Examples 7-9, indicating that there is a synergistic effect between glass fiber, carbon fiber, bentonite and sodium alginate, which improves the mechanical properties, conductivity and wear resistance of glass fiber, and subsequently improves the corresponding performance of the primer.

[0160] In the preparation method of modified graphene in Example 12, conductive silica is not added. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time is 10 minutes, the adhesion is level 1, the adhesion after water resistance is level 1, and there is no blistering or falling off, the impact resistance is 40 cm, and the flexibility is 2 mm, indicating that conductive silica can be loaded on the surface of graphene to improve the hardness, toughness and adhesion of the system. The subsequent application in primer not only improves the conductivity of the primer, but also increases the hardness, wear resistance and adhesion of the primer.

[0161] In the preparation method of modified graphene in Example 13, modified lignin is not added. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time is 12 minutes, the adhesion is level 1, the adhesion after water resistance is level 1, and there is no blistering or falling off, the impact resistance is 40 cm, and the flexibility is 2 mm, indicating that the modified lignin has a certain viscosity, so that the conductive white carbon black and graphene are closely bonded, thereby making the performance of the modified graphene stable, enhancing the toughness and strength of the graphene, and subsequently improving the corresponding performance of the primer.

[0162] Example 15 changes the mass ratio of graphene, conductive silica and modified lignin. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time, impact resistance and flexibility performance tests are all worse than those of Example 1, but better than those of Examples 12-13, indicating that the combination of graphene, conductive silica and modified lignin has a synergistic effect, and the subsequent application in primer not only improves the conductivity of the primer, but also increases the hardness, wear resistance and adhesion of the primer.

[0163] In the preparation method of the modified lignin in Example 16, no nano-silver powder is added, and in the preparation method of the modified lignin in Example 17, no polyvinyl alcohol is added. As can be seen from Table 1, relative to Example 1, the surface dry conductivity time, impact resistance and flexibility tests are all worse than those in Example 1 to varying degrees, but better than those in Example 13, indicating that the nano-silver powder can be loaded on the surface and pores of lignin to improve the antibacterial and electrical conductivity of lignin, and polyvinyl alcohol and lignin can form a network structure through physical cross-linking, increase the mechanical strength and toughness of the system, and thereby effectively improve the corresponding properties of the primer.

[0164] Example 19 changes the mass ratio of lignin, nano-silver powder and polyvinyl alcohol. It can be seen from Table 1 that, relative to Example 1, the surface dry conductivity time, impact resistance and flexibility performance tests are all worse than those of Example 1, but better than those of Examples 16-17, indicating that polyvinyl alcohol and lignin can form a network structure through physical cross-linking, so that the nano-silver powder and lignin are tightly bonded, thereby improving the viscosity, mechanical properties and conductivity of the modified lignin, thereby effectively improving the corresponding performance of the primer.

[0165] Comparative Example 1 does not add modified porcelain clay. As can be seen from Table 1, the surface dry conductivity time is 15 minutes, the adhesion is level 3, the adhesion after water resistance is level 3, and there is blistering, partial shedding, impact resistance is 30 cm, and flexibility is 9 mm, indicating that the modified porcelain clay improves the adhesion of the primer coating, and can also increase the hardness, wear resistance and scratch resistance of the primer coating.

[0166] Comparative Example 3 does not add modified graphene. As can be seen from Table 1, the surface dry conductivity time is 18 minutes, the adhesion is level 3, the adhesion after water resistance is level 3, and there is blistering, partial shedding, impact resistance is 30 cm, and flexibility is 11 mm, indicating that the modified graphene has high strength and high toughness, and can enhance the mechanical properties of the primer coating, such as wear resistance, crack resistance and adhesion.

[0167] In Comparative Example 2 and Comparative Example 4, the modified china clay is replaced by an equal amount of china clay and the modified graphene is replaced by an equal amount of graphene, respectively. As can be seen from Table 1, the surface dry conductivity time, adhesion, impact resistance and flexibility are all worse than those in Example 1, but better than those in Comparative Example 1 and Comparative Example 3, indicating that the modified china clay and graphene in the present application have better adhesion and mechanical properties, and the obtained primer has better comprehensive performance.

[0168] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A water-based one-component PP conductive primer, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of waterborne epoxy resin, 20-30 parts of conductive mica powder, 45-55 parts of deionized water, 3-5 parts of conductive carbon black, 15-20 parts of modified china clay, 5-8 parts of nano silicon dioxide, 0.1-0.6 parts of modified graphene, 3-5 parts of silane coupling agent, 3-8 parts of ethyl acetate, 0.5-1 parts of leveling agent and 0.5-1 parts of defoaming agent; The preparation method of the modified porcelain clay comprises the following steps: (1) calcining the clay at 500-600°C for 2-3h, dispersing the clay in deionized water, adding sodium humate, ball milling for 6-8h, sieving, washing with water, and drying to obtain pretreated clay; (2) crushing the modified glass fiber, sieving it, and then dispersing it in deionized water, adding the china clay pretreated in step (1), stirring for 2-3 hours, filtering, spraying the chitosan solution on the surface, and drying it to obtain modified china clay; The preparation method of the modified glass fiber comprises the following steps: dispersing the glass fiber in a sodium hydroxide solution, stirring for 20-30 minutes, washing with water, and then dispersing in deionized water, adding carbon fiber, bentonite and sodium alginate, stirring at a temperature of 90-95° C. for 2-3 hours, and drying to obtain the modified glass fiber; The preparation method of modified graphene comprises the following steps: (1) dispersing graphene in a formic acid solution, ultrasonically treating for 1-2 hours, washing with water, and then dispersing graphene in deionized water, adding sodium dodecylbenzene sulfonate, and ultrasonically treating for 2-3 hours to obtain a mixed solution; (2) Dispersing conductive white carbon black in butanol, stirring evenly, adding the mixed solution of step (1), ultrasonicating for 2-3 hours, then adding modified lignin, stirring at 40-45° C. for 2-3 hours, and drying to obtain modified graphene; The preparation method of the modified lignin comprises the following steps: dispersing the lignin in a sodium hydroxide solution, stirring at 80-85°C for 1-2 hours, adding dimethylphenol, reacting for 1-2 hours, filtering, washing with water, then dispersing in an acetic acid solution, adding nano silver powder and polyvinyl alcohol, stirring for 1-2 hours, and drying to obtain the modified lignin.

2. A water-based one-component PP conductive primer according to claim 1, characterized in that: The mass ratio of the china clay, the modified glass fiber and the chitosan solution is 1:0.2-0.4:0.05-0.

07.

3. A water-based one-component PP conductive primer according to claim 1, characterized in that: The mass ratio of the glass fiber, the carbon fiber, the bentonite and the sodium alginate is 1:0.2-0.4:0.1-0.3:0.07-0.

09.

4. A water-based one-component PP conductive primer according to claim 1, characterized in that: The mass ratio of the graphene, conductive white carbon black and modified lignin is 1 mg: 3-5 g: 0.2-0.4 g.

5. A water-based one-component PP conductive primer according to claim 1, characterized in that: The mass ratio of the lignin, nano silver powder and polyvinyl alcohol is 1:0.3-0.5:0.04-0.

07.

6. The method for preparing a water-based one-component PP conductive primer according to claim 1, characterized in that: The steps include: Conductive mica powder, conductive carbon black, modified china clay, nano silicon dioxide and modified graphene are mixed and ground to obtain a mixture; Evenly mix water-based epoxy resin, deionized water, silane coupling agent, ethyl acetate, leveling agent and defoaming agent, add the mixture, and stir for 2-3 hours at a stirring speed of 2000-2200 r / min to obtain a water-based one-component PP conductive primer.

Citation Information

Patent Citations

  • Graphene static-conducting priming paint and preparation method thereof

    CN109777214A